The Outcome of HyperCVAD Combined with Alemtuzumab for the Treatment of Aggressive T-Cell and NK-Cell Neoplasms. - Kuan, Jew-Win; Chang, Kian-Meng; Lau, Ngee Siang; Visalachy, Purushothaman; Tan, Sen Mui; Ong, Tee Chuan; Su, Anselm-Ting (Elsevier Ltd., 2011)
We report our experience in using six cycles of hyperCVAD in combination with alemtuzumab for the treatment of aggressive T-cell and NK/T-cell neoplasms. Seven females and six males with the median age of 41 (range 18–60) diagnosed with T-cell acute lymphoblastic lymphoma and peripheral T-cell and NK/T-cell neoplasms (nPTCL = 6, nT-cell ALL = 3, nNK/T-cell neoplasms = 4) from 2006 to 2008 were treated with alemtuzumab–hyperCVAD regimen. A total of nine patients (69%) responded to the regimen, with seven achieved complete remission and two achieved partial remission. The median progression free survival and overall survival duration among the responders with complete remission were 12.9 and 24.9 months respectively. The incidence of relapse among the responders was 44% and the overall survival rate was 23%. Only four (31%) patients completed the six cycles of alemtuzumab– hyperCVAD. Others were stopped earlier due to progressive disease (n = 2), cytomegalovirus (CMV) reactivation and/or disease (n = 3), death not due to disease (n = 2), and patient’s refusal to continue alemtuzumab (n = 2). The incidence of death not due to disease, CMV reactivation and recurrent CMV reactivation were 50, 50 and 17%, respectively. This study shows that alemtuzumab in combination with hyperCVAD regimen is a feasible regimen but with high toxicity. The toxicity might be reduced with the incorporation of filgrastim and use of valganciclovir as CMV prophylaxis.